(untitled) (Research, Society and Development, 2021)
This article presents the scope review protocol on Brazilian scientific production on ethnobotany. And it aims to document the processes involved in the planning and methodological conduct of this unprecedented study, examining the extent, scope and nature of research activities in ethnobotany in Brazil with a view to identifying possible research gaps in the existing literature. This review will be conducted following the guidelines of the Joanna Briggs Institute (JBI) and prepared in accordance with the items of the PRISMA Extension for Scoping Reviews (PRISMA-ScR): Checklist and Explanation. To this end, scientific articles published in the following languages ​​will be selected and reviewed: English, Portuguese and Spanish in the following databases: Web of Science, PubMed /Medline, Lilacs/BVS, Scopus, and Scielo. This protocol has been registered in the Open Science Framework (OSF), under doi: 10.17605/OSF.IO/N4XD3. It is hoped that this study will map and demonstrate the scenario and panorama of ethnobotanical studies carried out in Brazil, which may guide the conduct of future research on this topic in our country.